Multi-Mode Total Focusing Method (MTFM) to Detect High-Temperature Hydrogen Attack (HTHA) – A Review - Oktikawati, Anjar; Riastuti, Rini; Yuanto, Nursidi (UI Scholars Hub, 2023)
High temperature hydrogen attack (HTHA) is a commonly observed harm component in carbon steels exposed to high temperature and pressure in a hydrogen-rich environment. Hydrogen together with carbon responds to produce methane. The formation of methane bubbles in steel can lead to loss of fracture toughness and lead to intergranular cracking. The main challenge of this problem lies in early warning systems that can detect these bubble clusters before they reach the advanced stage. Several advanced ultrasonic inspections have been developed over the years due to the challenges of inspecting materials for defects and discontinuities. These cover time-of-flight diffraction (ToFD), phased array ultrasonic testing (PAUT), total focusing method (TFM), multi-mode total focusing method (MTFM), and others. However, these ultrasonic techniques used are typically used to detect all possible material defects. This paper briefly discusses the advantages and disadvantages of these techniques. MTFM has been successfully applied to characterize isolated or clustered signs, whether tilted or not, using high-frequency probes. The defects grouped in this paper are believed to be methane bubbles or HTHA. ToFD defect screening before aims to save time and money.